Anodizing Characteristics of AA1100 in 20% Sulfuric–Phosphoric Acid Electrolytes under Aerated and Non-Aerated Conditions at Various Times - Tri Hariyadi; Tita Rosita; Aniqa Arjumand Bano Harvani; Silvia Fatimatur Rahmawati; Tifa Paramitha; Alfiana Adhitasari; Rony Sihombing (Journal of Green Science and Technology, 2026)
Aluminum alloy AA1100 exhibits good corrosion resistance but suffers from low surface hardness and wear resistance, which can be improved through anodizing. However, limited studies have examined the combined influence of sulfuric–phosphoric acid electrolyte composition and aeration. This study investigates the effect of sulfuric–phosphoric acid electrolyte composition and aeration on oxide layer mass, thickness, and hardness during anodizing. Anodization was conducted using a total electrolyte concentration of 20% with varying sulfuric acid (15–20%) and phosphoric acid (5–0%) ratios at a current density of 3 A/dm², operating times of 15 and 30 minutes, and room temperature under aerated and non-aerated conditions. The results show that aeration significantly increased oxide layer formation, yielding an average oxide mass of 0.0173 g compared to 0.0106 g in non-aerated systems. The maximum oxide mass (0.0375 g) was obtained at 20% sulfuric acid with aeration for 30 minutes. The highest oxide layer thickness of 47.94 µm was achieved using a 19% sulfuric acid–1% phosphoric acid electrolyte under aerated conditions at 30 minutes. Meanwhile, the maximum surface hardness of 352.60 HVN was obtained at 15% sulfuric acid–5% phosphoric acid with aeration for 15 minutes. These findings demonstrate that electrolyte composition and aeration play a critical role in optimizing anodic oxide growth and mechanical properties of AA1100.